Household and meals versus the Temple purity system: Patterns of replication in Luke-Acts - Elliott, J. H. (Hervormde teologiese studies, 1991)
In Luke-Acts the social codes and concepts associated with food and meals replicate and support the contrasting social codes, interests, and ideologies associated with the Jerusalem Temple, on the one hand, and the Christian household, on the other. In this study the thesis is advanced that in contrast to the Temple and the exclusivist purity and legal system it represents, Luke has used occasions of domestic dining and hospitality to depict an inclusive form of social relations which transcends previous Jewish purity regulations and which gives concrete social expression to the inclusive character of the gospel, the kingdom of God, and the Christian community.